PENGARUH PENGGUNAAN MEDIA GAMBAR TERHADAP KEMAMPUAN MENULIS PUISI PADA SISWA KELAS X SMK SWASTA TERUNA PADANGSIDIMPUAN - Dalimunthe, Fatma Hayati; Hasibuan, Nikmah Sari; Lubis, Khatib (Universitas Muhammadiyah Tapanuli Selatan, 2024)
AbstractÂ This research aims to determine the influence of using visual media on students' ability to write poetry in the 10th grade of Teruna Padangsidimpuan Private Vocational School. The method used is quantitative research. The population of the study consists of 10 classes with a total of 285 students, and the sample is taken from the Machining Engineering class, totaling 33 students. Data collection technique involves 10 multiple-choice test questions (variable X) and 5 essay test questions (variable Y). Data analysis is conducted using the Pearson product-moment correlation formula